Merenungi makna keberadaan manusia di era modern - Zahra, Ghefira Az (Maliki Interdisciplinary Journal, 2024)
In this modern era, the meaning of human existence can be seen from the perspective of various philosophical theories, such as idealism, materialism, and also the views of Islamic scientists. The philosophy of idealism emphasizes the power of human thought and consciousness as the core of reality, while materialism focuses on physical aspects and material processes in determining human existence. The Islamic view emphasizes the physical, spiritual and intellectual dimensions of humans. Apart from that, this article also discusses mind-body problems and the role of symbols and ethics in human life. In the modern era, the development of artificial intelligence (AI) brings new challenges in understanding human existence, including the social, economic and ethical impacts it causes. In conclusion, to maintain a balance between technological developments and human values, deep understanding and strict ethical supervision are needed.